Ice thickness measurements and volume estimates for glaciers in Norway - Andreassen, Liss M.; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Melvold, Kjetil; Elvehøy, Hallgeir; Winsvold, Solveig H. (Journal of Glaciology, 2015)
ISSN:0022-1430 ISSN:1727-5652